Pengaruh Inokulasi Dua Spesies Cendawan Mikoriza Arbuskula dan Pemupukan Fosfor terhadap Pertumbuhan dan Serapan Fosfor Tajuk Bibit Kelapa Sawit ( Elaeis guineensis Jacq.) - Ade Wachjar; Yadi Setiadi; Ninin Yunike (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2002)
The objective of this experiment was to evaluate the effect of two Arbuscular Mychorrhizal Fungi (AMF) species and phosphorus fertilization on growth and shoot P-uptake of oil palm seedling. Experiment was conducted from September 1999 to March 2000 at Darmaga, the Cikabayan Experiment Station of Bogor Agricultural University. The experiment was arranged in Randomized Bloqk Design with five replications. The first factor was species of AMF. consisted of without AMF. inoculation with Glomus aJlJlreJlatum (OG-I05) and inoculation with Glomus manihotis (INDO-I). The secondfactor was dosage of phosphorus consisted of 0, 0.577, 1.154 and 1.734 g P/seedling.The Arbuscular Mycorrhizal Fungi did not increase height of seedling, leaves total (except on leaves total at 28 weeks after planting), shoot biomass, total biomass. and shoot P-uptake compare to the control. Shoot P-uptake was significantly decreased on seedling which was inoculated with G. manihotis compare to inoculated G. aJlJlreJlatum and control. Phosphorus fertilizer and it's interaction with species of AMF did not give any influence on growth and shoot P-uptake of the oil palm seedling. Keywords.. Mycorrhizal fungi. Phosphorus fertilization, Oil palm